2015
DOI: 10.2174/1871527315666151111123319
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aerobic Exercise on Cognitive Function of Alzheimer’s Disease Patients

Abstract: To evaluate the effect of moderate intensity of aerobic exercise on elderly people with mild Alzheimer's disease, we recruited fifty volunteers aged 50 years to 80 years with cognitive impairment. They were randomized into two groups: aerobic group (n=25) or control group (n=25). The aerobic group was treated with cycling training at 70% of maximal intensity for 40 min/d, 3 d/wk for 3 months. The control group was only treated with heath education. Both groups were received cognitive evaluation, laboratory exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 0 publications
2
99
1
1
Order By: Relevance
“…The exercise intervention was arranged for the participants requiring long-term care based on previous studies. [1][2][3][4][5][6][7][8][9][10] The exercise time was made shorter compared with previous studies, taking into consideration that the participants are nursing home residents who require long-term care and have cognitive dysfunction. We organised the exercise class so that the participants could easily understand and enjoy the activities.…”
Section: Exercise Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exercise intervention was arranged for the participants requiring long-term care based on previous studies. [1][2][3][4][5][6][7][8][9][10] The exercise time was made shorter compared with previous studies, taking into consideration that the participants are nursing home residents who require long-term care and have cognitive dysfunction. We organised the exercise class so that the participants could easily understand and enjoy the activities.…”
Section: Exercise Interventionmentioning
confidence: 99%
“…Previous studies have shown the favourable effects of exercise on cognitive function and physical activity. [1][2][3][4][5][6][7][8][9] On the other hand, the Lifestyle Interventions and Independence for Elders (LIFE) study, a 24-month physical activity program, has shown no improvements in global or domain-specific cognitive function among sedentary older adults. 10 Most of these previous studies are communitybased studies.…”
Section: Introductionmentioning
confidence: 99%
“…While more than one-third of the interventions were beneficial, 14 out of 26 controls significantly decreased. Descriptions of intervention and control groups included in the review are presented in Table 3 [29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54]. All of the included studies were considered to have had a good methodological quality, scoring between 7 and 9 points according to the PEDro.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Dementia/Mild Cognitive Impairment: Aerobic-Type Exercise Generally Provides Cognitive Benefits. Among those already cognitively impaired, most prospective exercise trials documented significant cognitive benefits [146][147][148][149][150][151][152][153][154][155] ; however, a few reported only modest outcomes, [156][157][158] with 1 negative study. 159 The most recent metaanalysis assessing RCTs of aerobic exercise in demented patients reported significant positive effects on cognition.…”
Section: Establishedmentioning
confidence: 99%